The role of mitochondria in aging, cell death, and tumor immunity - Wang, Qiang; Yuan, Yixiao; Liu, Jing; Li, Chunhong; Jiang, Xiulin (Frontiers in Immunology, 2024)
Mitochondria are essential double-membrane organelles with intricate structures and diverse functions within cells. Under normal physiological conditions, mitochondria regulate cellular metabolism and maintain energy homeostasis via the electron transport chain, mediate stem cell fate, and modulate reactive oxygen species production, playing a pivotal role in energy supply and lifespan extension. However, mitochondrial dysfunction can lead to various pathological changes, including cellular aging, necrosis, dysregulated tumor immunity, and the initiation and progression of cancer. Moreover, abnormal mitochondrial metabolism is closely associated with numerous diseases, such as neurodegenerative disorders, metabolic syndromes, and cancers. In recent years, targeting mitochondria has emerged as a promising anticancer strategy, aiming to modulate mitochondrial functions and metabolism for therapeutic benefits. Nonetheless, such approaches face limitations, including low delivery efficiency and insufficient specificity. This review systematically explores mitochondrial structure and function, their physiological and pathological roles, and the potential and challenges of mitochondria-targeted strategies in cancer therapy, providing insights for future research directions.